Boron-doped ordered mesoporous carbons for the application of supercapacitors. (20th July 2016) - Gao, Jiao; Wang, Xianyou; Zhang, Youwei; Liu, Jia; Lu, Qun; Liu, Min
Highlights: The BOMCs are prepared by nanocasting approach. The obtained BOMCs maintain the ordered mesostructure. The high specific capacitance of 267.8 F g −1 is achieved for BOMC-0.05. Abstract: The boron-doped ordered mesoporous carbons (BOMCs) with different boron content are prepared by nanocasting approach using silica KIT-6, furfuryl alcohol and boric acid as the template, carbon and boron sources, respectively. The pore structure, morphology and surface physicochemical properties of the BOMCs samples are characterized by nitrogen adsorption/desorption isotherm, transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). The results demonstrate that BOMCs inherit the ordered mesostructure of the pristine OMC and possess some boron-doped species on the surface. The electrochemical performances of the BOMCs are characterized by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) test, electrochemical impedance spectroscopy (EIS) and cycle life measurement. It has been found that with the increase of the boron content, the BOMC-0.05 shows high specific capacitance of 267.8 F g −1 at the scan rate of 5 mV s −1 and low resistance. At the same time, the symmetrical supercapacitor using BOMC-0.05 as electrode shows a specific capacitance of as high as 69.8 F g −1 and excellent cyclic stability with the specific capacitance retention of 92% even after 10000 consecutive cycles. The remarkable electrochemical behaviors demonstrate that the BOMCs will be a promising electrode material for the application of supercapacitors.